Mobile Computing. - Garg, Kumkum (1900)
An undergraduate text on mobile computing, covering all the basic concepts of mobile computing as well as mobile communication. The book also deals with the new concepts that have emerged in recent years like Bluetooth Security and topics on Nokia Handhelds (a topic exclusive to this book).
WAP 2.0 security -- Summary -- Problems -- Multiple-choice questions -- Further reading -- Design andProgramming Projects -- Implementation of mobile IP -- Comparison between AODV and DSR protocols -- Bluetooth application -- Design of a WAP gateway -- Mobile agents for network monitoring -- An IEEE 802.11 LAN for a typical student hostel -- An application using wireless sensor networks -- Summary -- Problems -- Multiple-choice questions -- Further reading -- Appendices -- Appendix A -- Java programming language -- Socket programming -- Remote procedure call -- Remote method invocation -- Appendix B -- Index.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books